Nilai Ekologis dan Ekonomi Kawasan Sisen Ekosistem Lamun Kampung Syoribo dan Dafi di Pulau Numfor, Papua - Lisiard Dimara; Popi Ida Laila Ayer (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2021)
Sisen or Sasisen is a tradition of closing the sea by indigenous Biak tribes in Biak Numfor and Raja Ampat. The purpose of this study is: (1) assessing the chemical chemical quality of the waters of the seagrass ecosystem sisen region, (2) reviewing the ecological index of the sisen area of seagrass ecosystems; a) diversity of seagrass species, b) the structure of seagrass fish communities, (3) examine the role of sisen in the management of seagrass ecosystems, and (4) analysis of the economic value of seagrass sisen areas. The research methods used are surveying and data collection through interview techniques (questionnaires and FGD), direct analysis, line transect, quadrat plot and VES. The results of the research obtained are: (1) the chemical chemical quality of the waters of the seagrass ecosystem sisen area in Kampung Syoribo and Dafi, Numfor Island is in good condition and suitable for marine life; (2) the diversity of seagrass species is classified as moderate with a value of H' = 1.44; (3) the structure of the seagrass fish community consists of a) diversity of 2.62, b) density of 14.89 individuals/m2, c) uniformity of 0.81, and d) dominance of 0.02; (3) the role of sisen systems in the management of seagrass ecosystems is: a) excellent understanding of sisen (93%), b) awareness of the benefits of sisen is very good (100%), c) knowledge of the sisen area is very good (100%), d) very good in the application of sisen (97%), e) very good in complying with sisen regulations (90%), and f) participation rates keep the sisen area very good (93%); (4) the economic value of sisen seagrass area for: a) fishing activities IDR 116,192,104, b) Siganus spp fish farming IDR 103,185,055, c) seaweed cultivation IDR 17,152,021, d) beach tourism IDR 13,562,671, and e) snorkeling tourism to IDR 10,356,852. The application of sisen in seagrass ecosystem areas provides excellent ecological and economic benefits.Key Words: Ecology's Value; Economics Value; Sisen Areas; Numfor Island